Wohlstandspolarisierung, Verteilungskonflikte und Ungleichheitswahrnehmungen in Deutschland - Jürgen Faik; Jens Becker (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
– The connections between the polarization of living conditions, social conflicts concerning the distribution of resources and the perception of social inequality in Germany will be picked out as a central theme. By means of empirical findings it becomes clear that the degree of inequality and polarization with respect to the living conditions - both measured by the wellbeing indicator income - has increased in the Federal Republic of Germany during the recent past. This is accompanied by the fact that the perceived intensity of the socially especially important conflict between the poor and the rich has grown not only slightly. In this connection particularly for the disadvantaged groups - and beneath this in a pronounced manner for the (permanently) unemployed persons - there is a relatively high potential of dissatisfaction. Thisincludes some dangers for the democracy and the social stability in Germany although in an EU-27 perspective - at least in Western Germany - these dangers are rather ranked to a middle level which means that in this international relativity only a middle level of danger is indicated for (Western) Germany.
Keywords: D31; D63; D74; 330; Life-satisfaction; satisfaction with democracy